Oral presentation difficulties – Experience of students at a polytechnic in Sarawak - Gee Whai Kho, Marcus; Binti Abdullah, Nur Syafiqa Aqiera; Leong, Lai-Mei (Issues in Language Studies, 2015)
This study investigates areas of oral presentation difficulties experienced by students at a polytechnic in Sarawak. The participants of this study were 223 engineering and commerce students. The data were gathered through questionnaires and interviews. Findings from the data analysis show that the topmost predicament of the students in dealing with oral presentation is delivery, especially where language usage and anxiety management are concerned. Another aspect of the findings is that engineering students differ significantly from commerce students in coping with oral presentation difficulties such as preparation, organisation and delivery.